MOOC (Massive Open Online Courses) - Cvetković, Dragan (IntechOpen, 2022)
Massive Open Online Courses (MOOCs) are free online courses available to anyone who can sign up. MOOCs provide an affordable and flexible way to learn new skills, advance in careers, and provide quality educational experiences to a certain extent. Millions of people around the world use MOOCs for learning and their reasons are various, including career development, career change, college preparation, supplementary learning, lifelong learning, corporate e-Learning and training, and so on.